Praise as classroom communicative reinforcing device: perception of Haiphong University students - Đỗ, Thị Thùy Linh (ĐHNN, 2017)
Being urged by the situation, I would like to avail to myself of this opportunity to conduct a research study on students' perception of different types of teacher praise in a university in Vietnam to see whether it motivates or demotivates students in classroom communication.